2006
DOI: 10.1095/biolreprod.106.051375
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Hamster Sperm 26-Kilodalton Dehydrogenase/Reductase That Is Exclusively Localized to the Mitochondria of the Flagellum1

Abstract: Sperm mitochondria undergo remodeling during posttesticular maturation that includes extensive disulfide cross-linking of proteins of the outer membrane to form the insoluble mitochondrial capsule. The relationship of these changes to mitochondrial function in mature gametes is unclear. The phospholipid hydroperoxide glutathione peroxidase (GPX4; also termed PHGPx) represents a major disulfide bond-stabilized protein of the mitochondrial capsule, and it is readily released by disulfide-reducing agents. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Immunocytochemistry experiments repeatedly showed that P26h‐specific staining was restricted to the acrosomal cap of mature hamster spermatozoa (Berube & Sullivan, ; Begin et al , ; Legare et al , 1999 a ). By contrast, Nagdas, Winfrey & Olson () showed that hamster P26h was exclusively localized to the midpiece of spermatozoa from the cauda epididymis, while no staining was observed on the head region. Moreover, P26h was detected in total cauda sperm lysate but was absent in both the plasma membrane fraction of spermatozoa and cauda epididymal fluid, also in contrast to previous findings.…”
Section: Cbr2 a Carbonyl Reductase Closely Related To Dcxrmentioning
confidence: 92%
See 1 more Smart Citation
“…Immunocytochemistry experiments repeatedly showed that P26h‐specific staining was restricted to the acrosomal cap of mature hamster spermatozoa (Berube & Sullivan, ; Begin et al , ; Legare et al , 1999 a ). By contrast, Nagdas, Winfrey & Olson () showed that hamster P26h was exclusively localized to the midpiece of spermatozoa from the cauda epididymis, while no staining was observed on the head region. Moreover, P26h was detected in total cauda sperm lysate but was absent in both the plasma membrane fraction of spermatozoa and cauda epididymal fluid, also in contrast to previous findings.…”
Section: Cbr2 a Carbonyl Reductase Closely Related To Dcxrmentioning
confidence: 92%
“…It seems that both groups detected isoforms of hamster P26h, thus one possible explanation for their conflicting results might be the application of different fixation/permeabilization methods or different antibodies that were produced in‐house. The respective P26h proteins used for antibody production were either extracted from spermatozoa with detergent (Berube & Sullivan, ) or purified from isolated sperm tails (Nagdas et al , ). Interestingly, the antibodies from each group exclusively detected P26h in that particular region of the sperm from which the respective immunizing protein was extracted (sperm acrosome versus sperm flagellum).…”
Section: Cbr2 a Carbonyl Reductase Closely Related To Dcxrmentioning
confidence: 99%
“…2003). As well, glycolitic enzymes have been identified in the principal piece/flagellum in mammalian spermatozoa, including hexokinase, LDH and glyceraldehydes 3‐ phosphate dehydrogenase (GADP‐S) (Nagdas et al. 2005, 2006; Perl et al.…”
Section: Role Of Mitochondria In Sperm Physiologymentioning
confidence: 99%
“…The released sperm suspension was centrifuged at 100 g for 2 min at 4 8C. The pellet containing sedimented tissue fragments was discarded and supernatant centrifuged at 1500 g for 10 min at 4 8C to pellet spermatozoa (Nagdas et al 2006, Chakrabarty et al 2007. The pellets were washed twice in buffer containing 10 mM HEPES/NaOH and 100 mM NaCl and resuspended in the same buffer.…”
Section: Preparation Of Cauda Epididymal Whole Sperm Cell Fractionsmentioning
confidence: 99%
“…Mitochondria were isolated according to previously reported methods (Nagdas et al 2006). In brief, the washed pellets were suspended in buffer containing 10 mM HEPES/NaOH, 100 mM NaCl, and protease inhibitor cocktail (1:100 (v/v)).…”
Section: Isolation Of Mitochondria From Whole Cellmentioning
confidence: 99%